Experimental Study of Multilayer Beams of Lightweight Concrete and Normal Concrete. (2017) - Olmedo, F.I.; Valivonis, J.; Cobo, A.
Abstract: There are fibres work at compression and fibres work at tension in elements under bending actions. Even more, could be fibres which not work at all. This specific way of working leads since long time ago to the use of different materials inside a section or a non-quadrangular more efficient. This is the case of the reinforced concrete (concrete working at compression and steel at tensile) o the hallowed sections, T section or I section. It could take advantage of their mechanical characteristic using different types of concretes.